Neoliberalism, Mobility and Cook Islands Men in Transit - Alexeyeff, Kalissa (The Australian journal of anthropology, 2008)
From the 1990s, neoliberalism has been vigorously promoted by aid agencies operating in the Cook Islands. The solution to the country's economic problems has been sought in the privatisation of government assets and services and the development of free-market principles. Social Impact Assessment reports of these reforms have included information on their effect on women and children under the heading of ‘gender’; men, however, are notably absent as a category of analysis. Building on recent work about men, masculinities and development, this paper begins to address this imbalance by examining how Cook Islands men have been effected by, and how they react to, neoliberalism in a series of gender specific ways. In particular, it explores the relationship between masculinity, class, status, and migration.